Crossing the Pomerium The Boundaries of Political, Religious, and Military Institutions from Caesar to Constantine - Koortbojian, Michael 1952- (Princeton Princeton University Press, 2020)
Cover -- Contents -- List of Illustrations -- Acknowledgments -- Abbreviations -- Introduction: Antiquarian Reconstructions and Living Realities -- 1. Crossing the Pomerium: The Armed Ruler at Rome -- 2. Octavian's Imperium Auspiciumque in 43 bc and Their Late Republican Context -- 3. Roman Sacrifice and the Ritus Militaris -- 4. Constantine's Arch and His Military Image at Rome -- Bibliography -- Index of Ancient Texts -- Index of Inscriptions -- Index of Persons -- Index of Works of Art -- General Index.
Keywords: Civil-military relations-Rome